2008
DOI: 10.1111/j.1875-595x.2008.tb00357.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of Pakistani dentists in tobacco cessation

Abstract: Dentists exhibit a superficial approach to delivery of smoking cessation care. It is recommended that dentists be trained in delivering effective tobacco dependence intervention, using the WHO/FDI advocacy guide for oral health professionals, modified to incorporate gender oriented culturally sensitive doctor-patient interaction. Tobacco cessation clinics should also be set up in private and public sectors to augment the dentists' participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…Studies have highlighted the need for contribution of different healthcare professionals in resisting tobacco use [9]. A little number of smokers (4.93%) was found in our study, which is in consistent with other reported smoking prevalence among healthcare professionals [10] and inferior in comparison to the prevalence of smoking (20.3%) among dental professionals [11]. Smoking prevalence amongst health professionals is itself often a barrier for their participation in tobacco control.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Studies have highlighted the need for contribution of different healthcare professionals in resisting tobacco use [9]. A little number of smokers (4.93%) was found in our study, which is in consistent with other reported smoking prevalence among healthcare professionals [10] and inferior in comparison to the prevalence of smoking (20.3%) among dental professionals [11]. Smoking prevalence amongst health professionals is itself often a barrier for their participation in tobacco control.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are in accordance of several studies [20,21], that includes unavailability of good communication between dental office and smoking cessation programs. Another study reported that patient's gender acts as a barrier to execute smoking cessation activities [11]. The gender issue is in association with the religious influences prevailing in Pakistani society.…”
Section: Discussionmentioning
confidence: 99%
“…We had only 13.4% smokers compared with 20.3% reported by Mumtaz in 2008. 8 However, we had a significant number of participants that refused to answer the question. So it is difficult for us to estimate the prevalence of dentists who smoke.…”
Section: Discussionmentioning
confidence: 99%
“…This study also determined that most dentists feel that tobacco cessation counseling falls outside their domain of responsibility. 8 These results are backed by a study that asked patients if their dentist had ever talked to them about tobacco cessation, only 35% responded yes. 9 However, results from another study performed later in 2016 had relatively encouraging results, where 80% of the dentists recognized their role in tobacco cessation counseling and over 70% would offer help to patients that were willing quit.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco Use Insights n n Among the fifty six included studies, the majority (twenty-one) of the studies were conducted in South East Asia Region countries, followed by 9 studies in Eastern Mediterranean Region. A total of twenty six studies were conducted among dental students and interns, 3 [41][42][43] among dental hygienists, twenty two 27,[29][30][31][32][44][45][46][47][48][49][50][51][52][53][54][55][56] among dental practitioners, 3 [57][58][59] among pediatric dentists and 2 60,61 among oral surgeons (Table 1).…”
mentioning
confidence: 99%